MODEL INTERAKSI MULTI KULTUR DALAM RUANG VIRTUAL WHATSAPP: SILATURAHMI, KONFLIK, LEAVE GROUP - Aji Aditra Perdana; Dr. Irwansyah, S.Sos., M.A Dr. Irwansyah, S.Sos., M.A (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2019)
WhatsApp application allows each individual to interact free from the boundaries of space and time, but many problems in interaction appears. This study aims to find an interaction model in communicating via WhatsApp to Telco industry workers in Jakarta. The research is carried out qualitatively with observation and interview with WhatsApp users. The result shows that the multi-cultural interaction model in virtual space can be interwoven well if the user has a good literacy in communicating through WhatsApp. This study can provide learning to each individual that interacts on WhatsApp involving individuals in multiple cultures. Messages sent to virtual space can cause multiple perceptions because members are coming from different backgrounds. This study recommends the existence of multi-cultural literacy.